Association of haplotypes in the IL8 gene with susceptibility to chronic periodontitis in a Brazilian population - Kim, Yeon Jung [UNESP]; Viana, Aline Cavalcante [UNESP]; Curtis, Karen Maria C. [UNESP]; Orrico, Silvana Regina Perez [UNESP]; Cirelli, Joni Augusto [UNESP]; Mendes-Junior, Celso Teixeira; Scarel-Caminaga, Raquel Mantuaneli (Elsevier B.V., 2010)
Background: Interleukin 8 (IL-8) is a chemokine related to the initiation and amplification of acute and chronic inflammatory processes. Polymorphisms in the IL8 gene have been associated with inflammatory diseases. We investigated whether the - 845(T/C) and - 738(T/A) single nucleotide polymorphisms (SNPs) in the IL8 gene, as well as the haplotypes they form together with the previously investigated -353(A/T), are associated with susceptibility to chronic periodontitis.Methods: DNA was extracted from buccal epithelial cells of 400 Brazilian individuals (control n =182, periodontitis n=218). SNPs were genotyped by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Disease associations were analyzed by the chi(2) test, Exact Fisher test and Clump program. Haplotypes were reconstructed using the expectation-maximization algorithm and differences in haplotype distribution between the groups were analyzed to estimate genetic susceptibility for chronic periodontitis development.Results: When analyzed individually, no SNPs showed different distributions between the control and chronic periodontitis groups. Although, nonsmokers carrying the TTA/CAT (OR = 2.35, 95% CI = 1.03-5.36) and TAT/CTA (OR= 6.05, 95% CI = 1.32-27.7) haplotypes were genetically susceptible to chronic periodontitis. The ITT/TAA haplotype was associated with protection against the development of periodontitis (for nonsmokers OR= 0.22, 95% CI = 0.10-0.46).Conclusion: Although none of the investigated SNPs in the IL8 gene was individually associated with periodontitis, some haplotypes showed significant association with susceptibility to, or protection against, chronic periodontitis in a Brazilian population. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Interleukin-8; Periodontitis; Polymorphism; Haplotype